1968
DOI: 10.2307/1934472
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Carbon Dioxide Under the Snow in the Arctic

Abstract: Atmospheric carbon dioxide was monitored continously by infrared analysis near Barrow, Alaska, from September, 1965 to July, 1966. The purpose of these measures was to determine the fluctuations of carbon dioxide under the snow cover. Average daily surface values of carbon dioxide as measured at the tundra surface increased a few days after the first snowfall. High and variable values occurred until early December and then decreased to lower, relatively stable concentrations that persisted to early May. At tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 1 publication
6
57
1
1
Order By: Relevance
“…Efflux from wet sedge ecosystems (circles) followed soil surface temperature closely, and increased exponentially as soil surface temperature increased, while efflux from tussock tundra ecosystems (squares) followed soil surface temperature nearly logarithmically ( Figure 5). These data, although collected during the arctic cold season, are not qualitatively different than temperature response curves of microbial populations reported during the warm season and suggest a biogenic source for the cold season CO2 loss [Kelley et al, 1968;Zirnov et al, 1993]. However, although them appears to be a correspondence between soil surface temperature and ecosystem respiration, it is unknown whether the net CO 2 efflux observed during November and March was due to current biological activity, as temperatures throughout the soil profile were well below the presumed threshold for biological activity (see below).…”
Section: Soil Temperature Profiles and Thaw Depthcontrasting
confidence: 53%
See 1 more Smart Citation
“…Efflux from wet sedge ecosystems (circles) followed soil surface temperature closely, and increased exponentially as soil surface temperature increased, while efflux from tussock tundra ecosystems (squares) followed soil surface temperature nearly logarithmically ( Figure 5). These data, although collected during the arctic cold season, are not qualitatively different than temperature response curves of microbial populations reported during the warm season and suggest a biogenic source for the cold season CO2 loss [Kelley et al, 1968;Zirnov et al, 1993]. However, although them appears to be a correspondence between soil surface temperature and ecosystem respiration, it is unknown whether the net CO 2 efflux observed during November and March was due to current biological activity, as temperatures throughout the soil profile were well below the presumed threshold for biological activity (see below).…”
Section: Soil Temperature Profiles and Thaw Depthcontrasting
confidence: 53%
“…The cold season efflux is attributed to respiration of cold-tolerant soil microorganisms [Kelley et al, 1968;Coyne and Kelley, 1974;Zimov et al, 1993] and CO2 loss from freezing soil during ice formation [Coyne and Kelley, 1971]. The primary decomposers in tundra soils are fungi, and most are considered cold-tolerant mesophiles which are able to respire heterotrophically at temperatures as low as-6.5 ø to -7.5øC [Flanagan and Bunnell, 1980].…”
mentioning
confidence: 99%
“…Furthermore, the timing of snowmelt influences the duration of the growing season and the active-layer thickness, which is also related to the amount of infiltrating snowmelt water into the soil. Goodrich (1982), Kelley et al (1968) and Groffman et al (2006) found that snow cover strongly influences the ground thermal regime. Using the ORCHIDEE (Organising Carbon and Hydrology In Dynamic Ecosystems) model, Gouttevin et al (2012b) showed that the snow cover and the disappearance of snow are important factors for the plant and soil metabolic activity and biogeochemical feedbacks between the soil and the atmosphere.…”
Section: A Ekici Et Al: Simulating High-latitude Permafrost Regionsmentioning
confidence: 99%
“…Explained by Fick's first law, the background theory of diffusion assumes that trace gas transport out of soils or through a snowpack occurs vertically, with the magnitude of fluxes determined by the concentration gradient . Advective transport from wind, however, can also affect the transport of trace gases such as CO 2 through porous media like soil and snow (Kelley et al, 1968;Janssens et al, 2001).…”
Section: Introductionmentioning
confidence: 99%